Dryas integrifolia subsp. integrifolia Vahl subsp. integrifolia - Desjardins, Émilie; Lai, Sandra; Payette, Serge; Dubé, Martin; Sokoloff, Paul C.; St-Louis, Annie; Poulin, Marie-Pier; Legros, Jade; Sirois, Luc; Vézina, François; Tam, Andrew; Berteaux, Dominique (Zenodo, 2021)
Dryas integrifolia Vahl subsp. integrifolia Figure 15A–C Materials examined. CANADA – Nunavut • Ellesmere Island, CFS Alert; 82°28′34″N, 062°26′49″W; 128 m a.s.l.; 2 Jul. 2019; habitat: barren ground, with till and rocks as substrates, and sparse dominance of Saxifraga oppositifolia QFA0635001. Identification. Plants 3–8 cm high; dwarf shrubs. Taproots and rhizomes present. Branches prostrate, sometimes rooting at nodes. Leaves evergreen; basal and cauline; isomorphic; alternate; petiolate. Stipules green or brown; hairy. Petioles 2–5 mm long; hairy, with white hairs. Leaf blades 4–9 mm long, 1–3 mm wide; lanceolate; bases cordate or truncate; unlobed; abaxial surface tomentose, with white hairs; adaxial surface shiny dark green, glabrous or sparsely hairy on the midvein; margins entire or slightly crenate, revolute, and glabrous; apices acute. Inflorescence a solitary flower. Pedicels 15– 25 mm long; erect; hairy with woolly hyaline hairs and dark purple glandular hairs. Epicalyx absent. Sepals 7 or 8; 3–7 mm long, 1–2 mm wide; linear or lanceolate; dark green; surface hairy, with woolly hyaline hairs and dark purple glandular hairs; margins ciliate; apices acute. Petals 8; 7–11 mm long, 3–5 mm wide; obtrullate or obovate; unlobed; white or ivory. Androecium with 40–70 stamens and 0.5–0.9 mm long anthers. Gynoecium consisting of numerous separate carpels, with 5–6 mm long conical styles. Fruit an achene, with elongate plumose styles. : Published as part of Desjardins, Émilie, Lai, Sandra, Payette, Serge, Dubé, Martin, Sokoloff, Paul C., St-Louis, Annie, Poulin, Marie-Pier, Legros, Jade, Sirois, Luc, Vézina, François, Tam, Andrew & Berteaux, Dominique, 2021, Survey of the vascular plants of Alert (Ellesmere Island, Canada), a polar desert at the northern tip of the Americas, pp. 181-225 in Check List 17 (1) on page 214, DOI: 10.15560/17.1.181